If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5 + -1x) + -1(6 + -4x) = 8x + -1(3x + -17) Remove parenthesis around (5 + -1x) 5 + -1x + -1(6 + -4x) = 8x + -1(3x + -17) 5 + -1x + (6 * -1 + -4x * -1) = 8x + -1(3x + -17) 5 + -1x + (-6 + 4x) = 8x + -1(3x + -17) Reorder the terms: 5 + -6 + -1x + 4x = 8x + -1(3x + -17) Combine like terms: 5 + -6 = -1 -1 + -1x + 4x = 8x + -1(3x + -17) Combine like terms: -1x + 4x = 3x -1 + 3x = 8x + -1(3x + -17) Reorder the terms: -1 + 3x = 8x + -1(-17 + 3x) -1 + 3x = 8x + (-17 * -1 + 3x * -1) -1 + 3x = 8x + (17 + -3x) Reorder the terms: -1 + 3x = 17 + 8x + -3x Combine like terms: 8x + -3x = 5x -1 + 3x = 17 + 5x Solving -1 + 3x = 17 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -1 + 3x + -5x = 17 + 5x + -5x Combine like terms: 3x + -5x = -2x -1 + -2x = 17 + 5x + -5x Combine like terms: 5x + -5x = 0 -1 + -2x = 17 + 0 -1 + -2x = 17 Add '1' to each side of the equation. -1 + 1 + -2x = 17 + 1 Combine like terms: -1 + 1 = 0 0 + -2x = 17 + 1 -2x = 17 + 1 Combine like terms: 17 + 1 = 18 -2x = 18 Divide each side by '-2'. x = -9 Simplifying x = -9
| 14+8(4x-7)=5x-10 | | 4.5p+.5=7.25 | | 2x^2+3x=-2 | | A+2B=435 | | 2x+9=4x+11 | | 4(2-2x)+2=6(2x-6)-4x | | s^2-3s-4=0 | | 8x-12=13+3x | | 2x-2=6x-10 | | 4(x-2)2=20 | | 6x^2-9= | | 3x+29=7x+9 | | 3x+4=8x-18 | | 10+3(x-2)= | | 5x^2+4-125=0 | | x^3=95 | | 7x^2=112 | | 7(r-4)=3(r-4) | | s^2=-14-9s | | -12+3x=x-6 | | 3-5[5-(6y-5)]= | | 2(b-7)=4(b-5) | | 16-44=6(x-1)-4 | | d=h-64 | | 7*ex=14 | | 22w=15 | | 5(8m+8)=-6(8+8m) | | 3p(p+5)=0 | | 1-3m=1-7m | | 7ex=14 | | 2(x-4)+3x=12 | | 7x-(2x-4)=19 |